Performance evaluation of forward osmosis and ultrafiltration membranes in harvesting Chlorella vulgaris - Muhammad, Defghi Arsy; Maharsih, Inggit Kresna; Nugroho, Wahyunanto Agung; Wibisono, Yusuf (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Chlorella vulgaris is a widely studied microalga due to its applications in food, pharmaceutical, and bioenergy sectors. Traditional harvesting methods often require chemical agents and energy-intensive processes. This study evaluates and compares two membrane-based harvesting technologies—Forward Osmosis (FO) and Ultrafiltration (UF) on key performance parameters: water flux, reverse solute flux (RSF), membrane fouling, biomass concentration, and energy/cost efficiency. The FO process, operated with varying NaCl draw solution concentrations (3–5 M), achieved maximum fluxes of 1735.3 LMH (FS) and 1930.4 LMH (DS), with the highest biomass yield of 10.8 mg/L. The UF process, using PVDF membranes, reached a peak flux of 4367.8 LMH and higher membrane fouling. While UF showed faster dewatering with lower electrical energy (50.6W vs. 136W), FO demonstrated lower fouling and potential for continuous sustainable operation. These findings inform optimization strategies for scalable, energy-efficient microalgae harvesting systems.